Prognozirovanie moshhnosti raboty na urovne maksimal'nogo potreblenija kisloroda pri ajerobnyh nagruzkah, primenjaemyh dlja gipertrofii skeletnoj muskulatury v silovyh vidah sporta - Miroshnikov, A.; Sidorov, E.; Smolensky, A. (Science in Olympic Sport, 2019)
It is known that aerobic exercises have a minimal effect on skeletal muscle mass, and therefore, compared with the results of studying the effect of strength exercises on musclefiber, there is an insufficient amount of scientific researches. In this work we attempted to compare the eff ectiveness of the impact on the rearrangement of muscle fiber of exercises performed through various, often opposed to each other, training means-exercises performed on the simulator for the so-called cyclic aerobic work (cycle ergometer) and strength exercises with a barbell. Data on the power of pedaling at the VO2max level can be obtained by measuring by a direct method, by gasometric analysis and a step test, or by using prognostic equations. The question of applying such equations, which could predict the power of pedaling, in revising the existing views on the impact of aerobic training in relation to the mass of skeletal muscles is very relevant, but among representatives of strength sports is insufficiently studied. Objective. Revision of existing views on the impact of aerobic training in relation to skeletal muscle mass based on the development and application of the prognostic equation for determining the power of pedaling at the VO2max level in representatives of strength sports events. Methods. Analysis and generalization of literary sources, pedagogical, biomedical methods, methods of mathematical statistics and regression analysis. Results. Analysis and generalization of the literary sources showed that correctly performed aerobic exercises lead to hypertrophy of skeletal muscles, which is comparable with strength training. It is proved that the developed prognostic equation helps to predict the pedaling power at the VO2max level while working on a bicycle ergometer and has a high correlation with the results of the direct measurement method, whereas the approach itself has several advantages over expensive testing procedures. Conclusions. In contrast to the existing view that aerobic work reduces the physiological cross-section of skeletal muscles, whereas strength one increases it, the paper shows that loads with weights and cyclic exercises are the means of recruiting muscle fibers, and the intensity of exercises (method or methodics) allows to trigger all the stimuli of muscle growth.